Association of Serum Uric Acid with Cardiovascular Diseases in Pakistani Adults: A Cross-Sectional Analysis: Serum Uric Acid with Cardiovascular Diseases in Pakistani Adults - Akhtar, Naheed; Haroon, Anita; Zafar, Madeeha; Ahmed, Mahnoor Khalil; Khan, Muhammad; Ahmed, Syed Zaryab; Latif, Noureen (Pakistan Journal of Health Sciences, 2025)
Numerous researchers have identified a strong link between increased levels of serum uric acid and cardiovascular disease. Objectives: To find out the association of serum uric acid with cardiovascular disease, independent of major confounding variables including age, sex, hypertension, diabetes, dietary habits, and lifestyle factors. Methods: A descriptive cross-sectional study was carried out at Fazaia Ruth Pfau Medical College. Data collection involved demographic, anthropometric, blood pressure, biochemical measurements, and electrocardiography. SPSS-22 was used for data analysis. Statistical methods included t-tests. one-way ANOVA, Mann-Whitney U test, and Pearson correlation were applied. To find the strength of association, a multivariate regression model was applied, and the odds ratio was calculated. Results: The frequency of hyperuricemia was 27.5%. Previous medical history of hypertension found a strong, significant association among the groups. The Frequency of cardiovascular diseases, including acute coronary disease, myocardial infarction, and cardiac failure, was 47%, 29.1% and 6% in the normouricemia group and 54.9%, 25.5% and 6.9% in the hyperuricemia group, respectively. Multivariate regression analysis revealed that the severity of cardiovascular diseases increased linearly with increasing serum uric acid concentration. Interestingly, the serum uric acid concentration was high in the cases of myocardial infarction in comparison to other cardiovascular diseases. The cardiovascular disease odds ratio was 1.84 to 2.45 times as the serum uric acid concentration rose above 9mg/dL. Conclusions: The Current study identified a significant association of hyperuricemia with cardiovascular diseases. The severity of cardiovascular diseases was observed to rise with increasing serum uric acid levels, and this link remained significant.